The Wealth Code 2.0 : How the Rich Stay Rich in Good Times and Bad. - Vanclef, Jason (Wiley, 2013)
A thoroughly revised and expanded update to the book that critics are calling the first true investing book for the ""new normal"" You entrusted your financial security to the "experts," and now you're wondering what it'll take to recover from the economic crisis and get back on your feet. In this updated and expanded edition of his critically-acclaimed guide to staying rich in good times and bad, financial planner and investment strategist Jason Vanclef delivers more straight answers and solid solutions-and he takes a well-earned poke or two at Wall Street in the process. Acc.